2016
DOI: 10.1590/01047760201622042242
|View full text |Cite
|
Sign up to set email alerts
|

Tree Community Composition and Aboveground Biomass in a Secondary Atlantic Forest, Serra Do Mar State Park, São Paulo, Brazil

Abstract: ABSTRAT Projects involving floristic-phytosociological surveys are becoming increasingly frequent and is a very important tool to access the biodiversity, status of succession, biomass and carbon storage, guiding conservation and management strategies. These studies are particularly important in Atlantic Forest, which is considered a hotspot in terms of biodiversity, endemism and impacts. São Paulo State lost more than 80% of original forest and, nowadays, remains only isolated patches with a variety stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
(69 reference statements)
0
17
0
4
Order By: Relevance
“…This is surprising considering that regrowth from clear felling could be considered a greater disturbance than selective logging and that the secondary plot contains ~68% of the intact plot biomass (Marchiori et al. ). This shows that despite recovery of some characteristics (e.g., biomass), logged forest can still show structural differences long after the logging event.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising considering that regrowth from clear felling could be considered a greater disturbance than selective logging and that the secondary plot contains ~68% of the intact plot biomass (Marchiori et al. ). This shows that despite recovery of some characteristics (e.g., biomass), logged forest can still show structural differences long after the logging event.…”
Section: Resultsmentioning
confidence: 99%
“…), and one in a regenerating area clear‐cut for charcoal production before park establishment that is considered a mid‐stage secondary forest (Marchiori et al. ). These plots are referred to as intact‐K, intact‐M, logged, and secondary in the text.…”
Section: Methodsmentioning
confidence: 99%
“…The study site (23.3254S, 45.0938W) is located within a 1‐ha permanent plot at 1,000‐m elevation. The vegetation is mid‐successional secondary forest, regenerating from clear felling for charcoal before the establishment of the park in 1977 (Marchiori, Rocha, Tamashiro, & Aidar, ). The forest is classified as montane moist dense forest (Vieira et al, ), mean annual precipitation is 2,300 mm with a dry season in July and August, mean annual temperature is 17 °C (Joly et al, ), and fog occurs frequently (Rosado, Oliveira, & Aidar, ).…”
Section: Methodsmentioning
confidence: 99%
“…Both Alchornea and Miconia are overstorey species, whereas Guapira is found in the subcanopy (Guilherme, Morellato, & Assis, ), and the species are ranked second, fifth, and sixth, respectively, in terms of abundance in the plot (Marchiori et al, ). All species are early successional (Marchiori et al, ) and are found in nearby old‐growth forest. Alchornea and Guapira are present at lower elevations in the park (Joly et al, ; Rosado, Oliveira, Joly, Aidar, & Burgess, ).…”
Section: Methodsmentioning
confidence: 99%
“…A contribuição percentual de palmeiras observada no presente trabalho foi próxima à verificada em outros trabalhos conduzidos em Floresta Ombrófila Densa (ALVES et al, 2010), que ficou em torno de 4 a 6%. Ressalta-se que a elevada abundância de Euterpe edulis¸ resultado também verificado por Marchiori et al (2016), é um indicativo do bom estado de preservação da mata nativa, visto que essa espécie está ameaçada de extinção devido à exploração predatória de palmito. O mesmo pode ser dito com relação a Astrocaryum aculeatissimum, cuja presença se encontra alarmantemente diminuída em fragmentos pequenos de Mata Atlântica devido a sua extração e baixo recrutamento, ocasionado pela diminuição na abundância de cotias (Dasyprocta agouti), pequenos roedores responsáveis pela sua dispersão natural.…”
Section: Discussionunclassified